Population Dynamics of Fall Armyworm (Lepidoptera: Noctuidae) in Maize Fields in Uganda - Ajam, Angella Lowra; Karungi, Jeninah; Ogwal,Geofrey; Otim, Michael Hilary (Insects, 2024)
Spodoptera frugiperda (Lepidoptera: Noctuidae), commonly known as fall armyworm, was first detected in Uganda in 2016 and has spread to all the maize-growing districts. Different methods have been deployed to control this pest. However, there is a limited understanding of the role of the environment and farmers’ practices on the abundance of and damage by S. frugiperda in Uganda. This study, therefore, assessed the abundance of S. frugiperda and leaf damage levels in three different districts and explored the association between agronomic practices, crop phenology, and weather parameters on S. frugiperda damage and abundance in smallholder farmers’ maize fields using a longitudinal monitoring survey in 69 farmers’ fields of Kole, Kiryandongo, and Nakaseke for three seasons. The numbers of egg masses and adults were generally low. The highest numbers of adults were trapped in Kiryandongo, followed by Nakaseke, and the lowest numbers were trapped in Kole. Leaf damage and incidence of damaged plants differed significantly between districts and seasons. Leaf damage and abundance of larvae varied significantly in the districts and at different growth stages. Conservation tillage, reduced weeding frequency, increased rainfall and high maximum temperatures were associated with reduced S. frugiperda damage. No significant relationship was observed between pesticide or cropping systems with S. frugiperda leaf damage. However, the influence of fertilizer use on leaf damage was contradictory across seasons and districts. Timely and vigilant scouting, proper timing of control measures, and minimum tillage practices should be included in an IPM strategy for S. frugiperda.